Management of Skin Allergy Due to Cosmetic Products -A Conceptual Study - Sharma, Monika; Sason, Rajveer; Charak, Sandeep (International Research Journal of Ayurveda & Yoga, 2021)
Beauty is a subject of social medical importance. Every person wants to stand at height and they require distinct personality which differ them from a crowd. People are using cosmetic products use for curing their skin problems and to maintain the skin appearance and beauty. Allergic reactions due to cosmetics may be delayed type reactions such as photo allergic contact dermatitis and immediate type reactions, that is contact dermatitis. Prick test is gold standard for diagnosis of allergy produce by cosmetic products. According to Ayurveda, if the body balance is maintained no allergic reactions are possible. All Skin disease have been described under Kustha (Psoriasis). Present paper highlights skin allergy produces by cosmetic products and its management through Ayurveda.